2013
DOI: 10.1002/open.201200039
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Boron‐Dipyrromethene (BODIPY) Dyes: Bright and Versatile Probes for Surface Analysis

Abstract: A family of bright boron-dipyrromethene-type fluorophores with a high number of fluorine atoms (F-BODIPYs) has been developed and characterized by X-ray crystallography and optical spectroscopy. The introduction of 3,5-bis(trifluoromethyl)phenyl and pentafluorophenyl moieties significantly enhances the photostability of such dyes, yielding for instance photostable near-infrared (NIR) fluorophores that show emission maxima>750 nm, when the BODIPY’s π system is extended with two (dimethylamino)styryl and (dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 87 publications
3
37
1
Order By: Relevance
“…The dynamic range of fluorometric methods is usually limited by effects of self-quenching at higher loadings, resulting in a deviation from linearity or even a reduction in the measured intensity. [22][23][24] The latter is not easily identifiable with commonly employed intensity-based (steady-state) instrumentation and can lead to an underestimation of surface functional groups. To account for such false negative results, different optical techniques like time-resolved fluorescence and absorption measurements need to be employed.…”
mentioning
confidence: 98%
“…The dynamic range of fluorometric methods is usually limited by effects of self-quenching at higher loadings, resulting in a deviation from linearity or even a reduction in the measured intensity. [22][23][24] The latter is not easily identifiable with commonly employed intensity-based (steady-state) instrumentation and can lead to an underestimation of surface functional groups. To account for such false negative results, different optical techniques like time-resolved fluorescence and absorption measurements need to be employed.…”
mentioning
confidence: 98%
“…Additionally, weaker broad absorption bands at shorter wavelengths can be assigned to S 0 −S n (n ≥ 2) transitions. [75][76][77][78][79][80][81][82] When the BF 2 moiety is removed from the BODIPY structure, the structure is converted into the all-trans conformation and the chromophore is converted into a type of cyanine dye. Cyanine dyes undergo trans-cis isomerization upon electronic excitation, which quenches the fluorescence.…”
mentioning
confidence: 99%
“…1 and Tables 1 and 2. Single crystal Xray structures that have been reported for 3styryl [60] and 3,5distyryl [61][62][63] BODIPY dyes have demonstrated that the transstyryl bonds shown in Scheme 1 for 3 are formed. The introduction of methylthio groups at the parapositions of the styryl groups provides scope for nanoparticle conjugation [64], and the mesomeric electron donating properties of the lone pairs on the sulfur atoms were expected to further enhance the red shift of the main spectral band [17].…”
Section: Synthesis and Characterizationmentioning
confidence: 98%